Designing Educational Media about the Inner Child for Adolescents Using Digital Illustrated Books - Absyir Abdul Wahhab; Damar Rangga Putra; Bayyinah Nurrul Haq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
Mental health issues are getting more attention since more people open themselves on social media related to psychological problems they experience. The problems they face are likely past traumas that carry over into adulthood. This paper is about designing an illustrated e-book that discusses the inner child or